Efficacy of micro-financing women's activities in Côte d'Ivoire: Evidence from rural areas and HIV/AIDS-affected women - Binaté Fofana, Namizata (Wageningen Academic Publishers, 2010)
This book deals with the effectiveness and the capability of microfinance institutions (MFIs) to enhance women's livelihoods and empowerment and to mitigate the effects of HIV and AIDS in Côte d'Ivoire. The results show that MFI credit causes positive and negative effects. MFI credit has improved incomes, the level of farm production and human and social capital. MFI credit has also enhanced women's decision-making power within households due to their new ability to contribute to the improvement of the household standard of living. Furthermore, women's empowerment regarding the demand for and the use of credit give them more opportunity to obtain MFI credit. Despite the positive effects of MFIs on women's income, this publication shows that loan repayment was not successful among some female borrowers due to the fact that the loan has not been used for investment purposes. For MFIs, the diversion of loans can endanger their functioning and sustainability and therefore their effectiveness in rural areas. Regarding HIV, this book highlights the diversity and the specificity of the way HIV-affected individuals are financially supported by credit institutions. Both the direct and indirect effects of HIV and AIDS on women's livelihood and MFIs are analysed.
Keywords: Infections transmisibles sexuellement et par le sang; OFDIG; VIH; afrique; côte d'ivoire; discipline; femmes*; finance; microfinance; régions géographiques; santé; sciences de la gestion; thématiques; économie

"Prolétaires de tous les pays, qui lave vos chaussettes?" Dialogue entre Delphy, Marx et les marxistes - Blais, Mélissa; Courcy, Isabelle (Nouveaux cahiers du socialisme, 2010)
Keywords: approches et analyses; capitalisme; cours; discipline; fem1000; féminisme matérialiste; militance; patriarcat; premier cycle; rapports sociaux de sexe; ressource en ligne; science politique et droit; sciences de la gestion; sciences humaines; sociologie; sofia; systèmes d'oppressions; thématiques; économie